ANALISIS STRATEGI PEMASARAN ONLINE DAN OFFLINE DALAM MENINGKATKAN PENJUALAN DAN KEBERHASILAN BISNIS PADA BUTIK KAYLA WATI - Kusniyah Kusniyah; Chandra Lukita; Ni Wayan Fitriana Ayu Lestari (CV. Denasya Smart Publisher, 2024)
The existence of this online media platform has a very dynamic and efficient role in supporting business activities. This study aims to determine the marketing strategy carried out by Kayla Wati Boutique Krangkeng Indramayu. This type of research is qualitative research with data collection techniques in the form of observation, interviews and documentation. The results showed that Kayla Wati Boutique's online system marketing strategy is to hold promotions on social media to attract consumer interest, the quality of goods or products displayed on social media must be exactly the same as the products to be sent to avoid consumer complaints.